A neutron diffraction and Rietveld analysis of cooperative Li motion in beta-eucryptite - Sartbaeva, A; Redfern, S; Lee, W (2004)
Li+ mobility and structural changes in the aluminosilicate beta-eucryptite have been studied by high-resolution powder neutron diffraction as a function of temperature from 573 to 873 K. A Li split-atom model was used to describe the disorder of Li+ ions in the structure. Analysis of the data shows two anomalies around 698 and 758 K. The first anomaly is attributed to an M-point zone boundary transition reported in the literature, which is connected to the appearance of the incommensurate structure. The second anomaly is attributed to a displacive phase transition of the framework and doubling in the a cell parameter.